Institutional representations and professional aspirations of Cadets in Portuguese Military Academies - Carreiras, Helena; Ávila, P.; Bessa, F.; Malheiro, L. (XIX World Congress of Sociology, 2018)
This presentation focuses on institutional representations and future career perspectives of on Portuguese military academies cadets. The study includes cadets from three branches of the Armed Forces (Army, Navy and Air-Force) and the National Gendarmerie. It draws on first results of an online survey conducted to all cadets in 2016 in the framework of a research project led by the Research Center of the Military University Institute (CIDIUM) and based on a civilian-military partnership. It addresses the issues of cadet’s perceptions about Armed Forces and it participation in the international missions as well as the perspectives about a future military career in a context of significant challenges to the military profession and the role of the Armed Forces in Portugal.